Kaji Eksperimental Pengaruh Massa Flywheel Terhadap Kinerja Kincir Air Dengan Sistem Transmisi Bertingkat Pada Saluran Irigasi - Ari Setiawan; Asral Asral; Musthafa Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
A study of flywheel mass variation is done in order to keeping the undershot waterwheel performance as a picohydro scale power plant. Testing is done with the available mass variation and in pair on each the four-shaft multilevel transmission system. From the test it is know that fluctuation of generator rotation decreases with increased flywheel mass, where the decrease of fluctuation occurred in flywheel mass 11.05 Kg and 14.63 Kg, while the constant rotation of the generator on the flywheel mass 26.54 Kg and 42 Kg. The optimal mounting position to reduce the fluctuation of rotation is the nearest position on the generator is on the fourth shaft. Influence of flywheel mass variation and mounting at transmission level, can be seen through the graph of fluctuation correlation of generator rotation with flywheel mass, indicates that the installation is on fourth shaft there was a decrease of fluctuation along with the addition of flywheel mass, so it affects the power generated generator.Keywords : Flywheel, Fluctuation, Waterwheel, Irrigation, Picohydro